Revisiting the Impact of Union Structures on Wages: Integrating Different Dimensions of Centralisation - Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
In a framework of a unionised oligopoly, this paper reconsiders the impact of the bargaining structure on union wages. In particular, two dimensions along which centralisation may occur, namely the professional and firm line, are integrated into one modelling framework. It will be shown that, when taking into account different centralisation dimensions, wage outcomes of different bargaining regimes cannot simply be ranked according to the degree of bargaining centralisation. The argument will be that negotiated wages rather depend on the technical relationship between different groups of labour and goods as well as upon the dimension along which centralisation takes place.
Keywords: J51; L13; 330; Unions; Bargaining Structure; Oligopoly; Lohn; Lohnverhandlungstheorie; Tarifpolitik; Gewerkschaftsorganisation; Theorie